Willing seduction : the blue angel, Marlene Dietrich and mass culture. - Kosta, Barbara (Film Europa, 2009)
Josef von Sternberg's 1930 film The Blue Angel (Der blaue Engel) is among the best known films of the Weimar Republic (1919-1933). A significant landmark as one of Germany's first major sound films, it is known primarily for launching Marlene Dietrich into Hollywood stardom and for initiating the mythic pairing of the Austrian-born American director von Sternberg with the star performer Dietrich. This fascinating cultural history of The Blue Angel provides a new interpretive framework with which to approach this classic Weimar film.